Electron Lenses for Super-Colliders - Shiltsev, Vladimir D. (Particle Acceleration and Detection, 2016)
This book provides a comprehensive overview of the operating principles and technology of electron lenses in supercolliders.  Electron lenses are a novel instrument for high energy particle accelerators, particularly for the energy-frontier superconducting hadron colliders, including the Tevatron, RHIC, LHC and future very large hadron colliders.  After reviewing the issues surrounding beam dynamics in supercolliders, the book offers an introduction to the electron lens method and its application.  Further chapters describe the technology behind the electron lenses which have recently been proposed, built and employed for compensation of beam-beam effects and for collimation of high-energy high-intensity beams, for compensation of space-charge effects and several other applications in accelerators. The book will be an invaluable resource for those involved in the design, construction and operation of the next generation of hadron colliders.